Between Rationalism and Empiricism - Scheibe, Erhard. author. aut Link
VIII, 627 p.
Keywords: Erhard Scheibe is one of the most outstanding German philosophers of science. He has written extensively on all the problems that confront the philosophy of mathematics and physics: rationalism versus empiricism, the laws of nature, and reductionism. He has published books on the logical foundations of quantum mechanics and on the reduction of physical theories. Little of his work has been translated into English. This collection of 38 essays is intended to remedy this omission and to help to make Erhard Scheibe's philosophical ideas better known to an international audience.